When giants learn to dance : mastering the challenge of strategy, management, and careers in the 1990s - Kanter, Rosabeth Moss. (London ; Boston, Mass. : International Thomson Buisness Press, 1989)
This book is about: Competing in the corporate olympics; Doing more with less; Jobs, Money, People; ...
Keywords: Management; Organization; Careers; Organizational change; Organizational effectiveness